2017
DOI: 10.1155/2017/6714307
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Interference from Swimming Pool Generator Current Causing Inappropriate ICD Discharges

Abstract: Electromagnetic interference (EMI) includes any electromagnetic field signal that can be detected by device circuitry, with potentially serious consequences: incorrect sensing, pacing, device mode switching, and defibrillation. This is a unique case of extracardiac EMI by alternating current leakage from a submerged motor used to recycle chlorinated water, resulting in false rhythm detection and inappropriate ICD discharge. A 31-year-old female with arrhythmogenic right ventricular cardiomyopathy and Medtronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…ICDs may encounter undesired shocks caused by the 60 Hz frequency of alternating current. This potential issue is also applicable to S‐ICDs 3,11,12 . Despite manufacturers implementing specific measures and precautions to address EMI in CIEDs, numerous case studies have reported instances where CIEDs administer inappropriate shocks due to EMI interference.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ICDs may encounter undesired shocks caused by the 60 Hz frequency of alternating current. This potential issue is also applicable to S‐ICDs 3,11,12 . Despite manufacturers implementing specific measures and precautions to address EMI in CIEDs, numerous case studies have reported instances where CIEDs administer inappropriate shocks due to EMI interference.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous instances of ICD malfunctions have been documented in the literature, underscoring the importance of comprehensively examining these occurrences for proper identification and proactive prevention 3,11,12 . An electromagnetic field may generate currents in the lead, resulting in local fibrillation or heating in the heart or induce voltage in the lead.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, given the growth of the Internet of Things (IoT), the potential for EM interactions is increasing. Sources of EM interference that caused patient illness included wireless networks [20], swimming pool generators [85], water pumps [86], electrostatic discharge from fleece clothing [87], co-existing implanted devices [88], surgical equipment [89], plastic toys [90], hot tubs [91], electrical installations [92] and consumer devices such as Fitbits [93]. Asher et al describe a case of a patient's e-cigarette interacting with an implantable cardioverter-defibrillator (ICD), and a 55F with an ICD which reverted to magnet mode due to interference with the patient's fitness watch [93].…”
Section: Electromagnetic Interference and Electric Smogmentioning
confidence: 99%
“…Electromagnetic interference (EMI) resulting in inappropriate implantable cardioverter-defibrillator (ICD) shocks or pacemaker inhibition is particularly dangerous while swimming 1 . Although incidents of EMI from alternating current (AC) electrical faults in pools have been described in the literature, they have been sporadic 2, 3, 4, 5. In this series, we describe a new source of EMI within saline chlorination/electrolytic pool cleaning systems.…”
Section: Introductionmentioning
confidence: 99%